Modelling the coupled heterogeneities of the lacustrine microbialite-bearing carbonate reservoir of the Yacoraite Formation (Salta, Argentina) - Teles, Vanessa; Hamon, Youri; Deschamps, Rémy; Rohais, Sébastien; Nader, Fadi H.; Heckenmeyer, Elodie; Gasparrini, Marta; Barbier, Mickael; Lerat, Olivier; Joseph, Philippe; Doligez, Brigitte (Comptes Rendus. Géoscience, 2023)
The Yacoraite Formation is a complex lacustrine microbialite-bearing carbonate formation whose heterogeneity is due to different sedimentary facies associations and several microbialite geobodies. The bi-variate plurigaussian geostatistical method is applied to simulate in parallel these two types of heterogeneity in a 3D reservoir-scale geological model. Each variable is simulated by a complete plurigaussian method based on geological interpretation and field observations and quantifications. They are coupled through the occurrence of the microbialites within the sedimentary facies and associated into combined facies giving a one-glance representation of the reservoir heterogeneity, then used to constrain the porosity simulation.